The Prevention of Sexual Abuse: An Evaluation of "Talking About Touching" - Madak, Paul R.; Berg, Dale H. (Canadian Journal of Counselling and Psychotherapy, 2008)
The program, "Talking About Touching," was designed to increase children's knowledge about sexual abuse, options to resist abusive situations, and to provide information about where to go for assistance if they have been abused. An evaluation of this program was conducted in five elementary schools and consisted of three components: (1) measurement of student knowledge in a pre-post design; (2) a survey of classroom teachers who delivered the program; and, (3) a survey of parents. The results indicate that: (1) although children in the study started out with a high level of knowledge related to sexual abuse, they made further statistically significant gains in knowledge; (2) teachers feel that the program is needed and that it has few negative side effects; and, (3) parents are generally supportive of the program and also report few negative side effects. Limitations of prevention program evaluations and areas for further research are discussed.